2019
DOI: 10.1051/e3sconf/201913602037
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric analysis of co-pyrolysis of coal and waste and used tires

Abstract: Waste tires can be used as a substitute for coal due to the high calorific value. In this study, the co-pyrolysis characteristics of the waste tires (truck tires, liners and nylon tires), pulverized coal and their blends are studied using thermogravimetric analyzer. The pyrolysis of truck tires, liners and coal is characterized by a three stages reaction while the pyrolysis of nylon tires and their blends are four stages. The pyrolysis characteristics of the blends can be expressed by the superposition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Figure S2 shows the variation of ΔW for all of the binary coal/additives mixtures. Some researchers have reported synergistic interactions in copyrolysis of coal and HDPE, 33 tires, 34 biomass, 29,35 and hydrochar. 36 In the present study, no notable synergism was found, with ΔW remaining practically constant (lower than ±1%.).…”
Section: Thermal Behavior Of Coal C Additives and Binary And Ternary ...mentioning
confidence: 99%
“…Figure S2 shows the variation of ΔW for all of the binary coal/additives mixtures. Some researchers have reported synergistic interactions in copyrolysis of coal and HDPE, 33 tires, 34 biomass, 29,35 and hydrochar. 36 In the present study, no notable synergism was found, with ΔW remaining practically constant (lower than ±1%.).…”
Section: Thermal Behavior Of Coal C Additives and Binary And Ternary ...mentioning
confidence: 99%
“…The surface of coal contains functional groups, 5,6 such as hydroxyl (OH), carboxyl (COOH), and ester (COOR) groups, which render coal hydrophilic and prone to agglomerate 7,8 . The modified coal exhibits excellent dispersion, improved compatibility with the matrix, and enhanced interfacial strength, which endow materials with superior thermal insulation, gas barrier, and mechanical properties 9–11 . Tan et al 12 modified coal by ball milling with four active agents which included silane coupling agent, aluminate coupling agent, sodium dodecylbenzene sulfonate, cetyltrimethylammonium bromide.…”
Section: Introductionmentioning
confidence: 99%